2022
DOI: 10.3389/fpubh.2022.962675
|View full text |Cite
|
Sign up to set email alerts
|

Pooled prevalence and determinants of informed choice of contraceptive methods among reproductive age women in Sub-Saharan Africa: A multilevel analysis

Abstract: BackgroundDespite the commitments of the government to minimize unintended pregnancy, abortion, and unmet need for contraceptives, as per our search of the literature, there is no study on the pooled prevalence and determinants of informed choice of contraceptive methods in sub-Saharan Africa. Therefore, this study aimed to assess the pooled prevalence and determinants of informed choice of contraceptive methods among reproductive-aged women in sub-Saharan Africa.MethodsThis study was based on the 32 Sub-Sahar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Compared to the age group of 25 to 34 years being age group between 35 and 49 years is found decrease the gap in informed choice of family planning between rural and urban residents. Other studies also reported similar findings [ 30 , 32 34 ]. The possible reason behind this could be elder mothers from rural areas may also seek more information about the family planning method that could be delivered to them because they might experience side effects and discomforts in their prior utilization of family planning methods.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Compared to the age group of 25 to 34 years being age group between 35 and 49 years is found decrease the gap in informed choice of family planning between rural and urban residents. Other studies also reported similar findings [ 30 , 32 34 ]. The possible reason behind this could be elder mothers from rural areas may also seek more information about the family planning method that could be delivered to them because they might experience side effects and discomforts in their prior utilization of family planning methods.…”
Section: Discussionsupporting
confidence: 81%
“…The reason for this could be the client flow at private health facilities are lower than at public health facilities so that informed choice of family planning can be practically achieved in private health facilities. Moreover, since private health facilities are commercial, they could have a good client handling approach including delivery of detailed information about the service and treatment they are providing to their clients [29][30][31]. It is better to expand private health facilities to rural areas as equal as the public health facilities to have informed choice services of FP.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, being in the age group 35 to 49 year was signi cantly narrowed the urban and rural gap in the informed choice of family planning where as being in the age group 25 to 34 found to widen the urban -rural gap of family planning compared to age group 15 to 24 year. Other studies also reported similar ndings (23,(25)(26)(27). The possible reason behind this could be elder mothers from rural areas may also seek more information about the family planning method that could be delivered to them because they might experience side effects and discomforts in their prior utilization of family plaining methods.…”
Section: Discussionmentioning
confidence: 64%
“…The reason for this could be the client ow at private health facilities are lower than public health facilities so that informed choice of family planning can be practically achieved in private health facilities. Moreover, since private health facilities are commercial, they could have good client handling approach including delivery of detail information about the service and treatment they are providing to their clients (22)(23)(24). In this study, being in the age group 35 to 49 year was signi cantly narrowed the urban and rural gap in the informed choice of family planning where as being in the age group 25 to 34 found to widen the urban -rural gap of family planning compared to age group 15 to 24 year.…”
Section: Discussionmentioning
confidence: 99%
“…There is a varied prevalence of informed contraceptive method choices across the globe [ 15 ]. Despite government objectives, a study conducted in 32 countries in SSA demonstrates that the prevalence of informed contraceptive method choice is low, with substantial country variations [ 16 ]. The low level of knowledge about contraceptive method choice in SSA is influenced by various factors, such as maternal age, residency, financial status, media exposure, internet use, marital status, education, occupational status, access to health facility, and access to contraceptives [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%